Photoemission spectroscopy of planar and nanostructured surfaces - Gervasoni, Juana Luisa (2016)
In this paper, I present some results for the process of excitation of bulk and surface plasmons during the emission of electrons in the proximity of surfaces of different shapes and dimensions. I describe in detail the effects due to the interaction between an electron and a stationary positive ion (or atomic hole) in the neighborhood of a metallic surface, paying special attention to the results obtained by my research group. We used the dielectric response of the metal and the specular reflection model for the case of planar surfaces, and the second quantization theory for nanostructured surfaces. In particular, we studied how the electron-hole pair interaction can influence the energy loss of the emerging electron. We investigated the importance of surface effects in the analysis of photoelectron spectroscopy. The method described here is useful for studying multiple plasmon excitations in nanostructures and for understanding the excited electron spectra of these nanostructures (different from those of the same bulk material).